Supercommunicators : how to unlock the secret language of connection [compact disc, unabridged] - Duhigg, Charles (Random House Audio, 2024)
Supercommunicators know the importance of recognizing, and then matching, each kind of conversation, and how to hear the complex emotions, subtle negotiations, and deeply held beliefs that color so much of what we say and how we listen. In this book, you will learn why some people are able to make themselves heard, and to hear others, so clearly. Charles Duhigg teaches the tips and skills we need to navigate conversations more successfully.